Timing Matters: Shifting Economic Activity and Intra-Day Variation in Ambient Ozone Concentrations - David Adler; Edson R. Severnini (Institute of Labor Economics (IZA), 2020)
Ground-level ozone has been shown to have significant health consequences from short-term exposure, and as such has been regulated in the U.S. since the 1970s by the Environmental Protection Agency (EPA). Ozone is not emitted directly; instead formation occurs due to a complex, Leontief-like combination of air pollutants and sunlight that results in high levels mid-day and low levels at night. Despite this known relationship, EPA regulations only consider the total emissions of ozone precursors and not when these emissions occur. Using hourly data on ambient ozone from 1980-2017 near the U.S. time zone borders, we provide evidence that the 1-hour time difference on either side of a border leads to a nontrivial change in ozone levels over the course of the day. We then examine a cap-and-trade program targeting ozone precursor emissions – the NOx Budget Program – finding that while it reduced ozone overall it did not have an economically significant effect on shifting when these emissions occurred. We conclude by outlining a possible policy solution to account for the time value of reductions in precursor emissions.
Keywords: Q53; Q58; 330; ambient ozone concentration; timing of ozone precursor emissions; time zone border; shifting economic activity; NOx Budget Program (NBP)